PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN SOFTWARE WINGEOM TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK - Alawiyah, Mufidah; Fajriana, Fajriana; Elisyah, Nur (LPPM UNIMAL, 2025)
The causes of low mathematical reasoning ability of students include the use of conventional learning models that are still used by teachers in the learning process, and minimal use of technology. Therefore, a solution is provided by implementing the Think Pair Share learning model assisted by Wigeom Software. The purpose of this study was to determine whether students' mathematical reasoning ability is influenced by the Think Pair Share learning paradigm assisted by Wingeom Software. This study used a nonequivalent control group posttest-only research design and was quasi-experimental. All participants in this study were students of class VIII MTs Negeri 2 Aceh Utara. Class VIII-B was chosen as the experimental class and class VIII-D as the control class using purposive sampling techniques. The instruments used were tests and observation sheets. The tests used were pretest and posttest to see students' mathematical reasoning ability and observation sheets to find out the activities of teachers and students in the learning process. Hypothesis testing in this study used a non-parametric test, namely the Mann Whitney U-test assisted by SPSS Version 22 Software with a significance level of 0.05. Asimp sig. 0.000 was found based on the findings of the posttest data hypothesis test on students' mathematical reasoning abilities. It can be concluded from the data hypothesis test criteria that students' mathematical reasoning skills are influenced by the Think Pair Share learning paradigm with the help of Wingeom Software